PENGARUH PENGETAHUAN, SANKSI, DAN KESADARAN PAJAK TERHADAP KEPATUHAN MAHASISWA UNISMA MEMBAYAR PAJAK KENDARAAN BERMOTOR - Ary Hutama Putra; Afifudin Afifudin; Siti Aminah Anwar (Universitas Islam Malang, 2021)
This study aims to determine the knowledge, sanctions, and awareness of taxes on the compliance of UNISMA students in paying motor vehicle taxes. The independent variables in this study are tacx knowledge, tax sanctions, and tax awareness. While the dependent variable is individual taxpayer compliance. This type of research, because the primary data with data collection methods in the form of a questionnaire via google form. The population in this study were students majoring in accounting, Daculty of Economics and Bussiness, University of Islam Malang, Class of 2017. The data collection technique used the slovin formula. Based on this method the number of students used there are 68 respondents. The hypotheses were tested using descriptive statistical analysis, instrument testing, normality testing, classical assumption test, multiple linear regression analysis, and hypotheses testing using SPSS tools. The results showed that the variables of understanding tax regulations, tax sanctions, and tax awareness had an effect on the compliance of UNISMA students in paying motor vehicle taxes. Keywords: Understanding of Tax Regulations, Tax Sanctions, Tax Compliance, Tax Awareness.